Solidarity Economy and Digital Territories: The Challenge of Participatory Technology Development for Traditional Communities in Amazonas - Souza de Alvear, Celso Alexandre (Cooperativismo & Desarrollo, 2025)
With the popularization of the internet and digital devices, information and communication technologies have become part of the daily lives of the vast majority of the population. In Brazil, usage that was once restricted to more privileged groups in urban centers can now be observed in the rural territories of the country's interior. This fact has been contributing to a phenomenon of digital transition in the field of the solidarity economy. Seeking to critically analyze the implications of this phenomenon, this article addresses the experience of the participatory development of a mobile application focused on the domestic economy of traditional communities in the interior of Amazonas, the region where the largest territorial expanse of the Brazilian Amazon Rainforest is located. The project was developed through a partnership between non-profit organizations that are part of the country's solidarity economy ecosystem, with the aim of supporting the organization of information related to productive activities carried out in the territories. The collection of information about the productive daily life intends, in the long term, to facilitate families' access to public policies for territorial protection, incentives for fishing, family agroecology, rural retirement, among others. The term Participatory Technology Development (PTD) is used to present the methodology employed. The reciprocal interaction between the actors involved in the process, which required the contribution of different types of knowledge, is discussed. To what extent do the farmers participate, and how are the results influenced by their participation?
Keywords: solidarity economy; digital territories; participatory technologies; traditional communities; digital inclusion